Gulf security and the U.S. military : regime survival and the politics of basing - Gresh, Geoffrey F., 1979- (Stanford security studies., 2015)
The U.S. military maintains a significant presence across the Arabian Peninsula but it must now confront a new and emerging dynamic as most Gulf Cooperation Council countries have begun to diversify their political, economic, and security partnerships with countries other than the United States-with many turning to ascending powers such as China, Russia, and India. For Gulf Arab monarchies, the choice of security partner is made more complicated by increased domestic and regional instability stemming in part from Iraq, Syria, and a menacing Iran: factors that threaten to alter totally the Gulf.